Exemplarische Analyse von Texttiteln im archäologisch-ideologischen Diskurs zur Ethnogenese der Slawen Zusammenfassung - Jachym, Barbara (Die deutsche Sprache in vielfältigen Forschungsparadigmen. Beiträge polnischer Doktoranden anlässlich der 9. Linguistischen Tagung–Łódź, 09.05.2015, 2016)
This article examines, under the selected aspects, the texts’ titles belonging to the archaeological and ideological discourse on ethnogenesis of the Slavs. An analysis of the titles show how much not only the content of the text but also the form of it and the titles themselves are under the historical and institutional framework building up an sociopolitical discourse. The period of time when the title was established is the one of the strong nationalist movement and a particular political situation. As the effect of the latter not only the press releases but also the scientific publications were not neutral against the mention earlier discourse but shows how powerful it was in the case of the titles.